Formation of land use within the water-conservation zones, protected shoreline belts and shorelines in cities - Tretiak, V.; Tretiak, N.; Kravchuk, T. (Land Management, Cadastre and Land Monitoring, 2020)
Annotation. Ukraine is at the next stage in completing land reform. Despite that, country gained independence, and still there are many unresolved and controversial land, environmental, water, urban development issues requiring additional state intervention. Incompleteness of land reform, in particularly some of the most important issues, one of which is the formation of land use within the water protection zones and coastal protection zones of cities, creates a negative ecological environment. And likewise, social tension in vital activity of population, especially for urban land use. In despite of the legislative ban, the construction within the water protection zones, coastal protection zones of cities continues. In addition, restrictions on the use of land and other natural resources located in this territory are also not formed. That is, their spatial placement has a huge impact not only on environmental, land and water relations, but also on economic, social and legal (rights guarantee).As a result of the study, was used data  from the public cadastral map of the State Service of Ukraine for  geodesy, cartography and cadastre, and an extract from the planning restrictions scheme of the General Plan of Kyiv. The information base for the study was the legislative and regulatory acts of Ukraine regarding the regulation of land, water and nature management, scientific works of world and domestic scientists, materials of scientific and practical conferences.As a result, the authors established formation features of land use within the water protection zones and coastal protection and coastal stripes of the city of Kiev. The essence of land use within such zones (strips) consist in the fact, that is as an ecosystem, combines several steeds of different purpose and functional use. In addition, urban land use within water protection zones, coastal protection zones and coastal strips, except environmental, legal, social, land relations, includes economic and water relations, which appears to be an important aspects in the effective regulation of such land use. Due to that, the choice was made to study formation features of urban land use within water protection zones and coastal protection and coastal strips. In order to ensure through land management and legal regulation of urban land use within the zones (strips) to increase the efficiency of its capitalization and greening.Keywords: urban land use, water bodies, water protection zones, coastal protection strips, coastal strips, land ownership.